First case of human latrodectism in Venezuela Primeiro caso de latrodectismo humano na Venezuela - Demetrio Kiriakos; Paola Núñez; Yasmely Parababire; Marianne García; Jenny Medina; Leonardo De Sousa (Revista da Sociedade Brasileira de Medicina Tropical, 2008)
The first case of envenoming by Latrodectus geometricus in Venezuela is described. The accident occurred at the victim's home, in Aragua de Barcelona, Anzoátegui State. The 31-year-old female victim was bitten twice on the left scapular region, in quick succession (within seconds). She developed a hyperactive state of the central, autonomic and peripheral nervous systems with minor local symptoms. Descreve-se o primeiro caso de envenenamento por Latrodectus geometricus na Venezuela. O acidente ocorreu na residência, em Aragua de Barcelona, Estado Anzoátegui. A paciente de 31 anos de idade foi picada, consecutivamente duas vezes, em segundos, na região escapular esquerda. Ela desenvolveu um quadro de hiperatividade do sistema nervoso central, autonômico e periférico com escassa sintomatologia local.